Materiales procedentes de un poblado del bronce final en Cástulo - Blázquez, J. M.; Valiente Malla, Jesús (Zephyrvs, 2009)
Near the remains of the ancien city of Castulo, at the cliffs that lay by the river Guadalimar, some layers with walls made of great boulders, floors of plate pebbles or mud with chalk plastering and several pottery fragments that seemed to be very old and presumably pre-Iberian, have been recently located. Prospected place and a sample of materials collected from the bottom of the cliffs, will be now reviewed in this paper. The walls are similar to those discovered in other miners settlements in Andalucía. The archaeological material collected covers a sample of almost a hundred of hand-made pottery fragments with several finishings: simple hand smoothing, «a la almagra» (indigenous red slip), burnishing and brushing. In addition, there is a minor sample of wheel-made pottery, which strictly belongs to a grey type («gris de Occidente»), with wheel-burnished surfaces. The study of this material suggests that there was a miners settlement near Castulo during the Late Bronce Age in the pre-Iberian time. That was indicated from the founds of copper slags and galena blocks, which appear in Linares nowadays. The final date of the settlement, as the scarce grey wheel-made pottery indicates, seems to have taken place about the middle of the seventh century B.C. The excavation, which began last summer, didn't reach to determinate the beginning date. However the authors of this paper hope fixing it after the digging end.